Navigating the Abyss of Trust and Mistrust: An Analysis of Maternal Relationships in 'We Need to Talk About Kevin' through Erik Erikson's Lens - Mohammad, Atef Ghalib (Thi Qar Arts Journal, 2024)
This paper examines the novel "We Need to Talk About Kevin" by Lionel Shriver in the context of Erik Erikson's first stage of psychosocial development, known as "Trust vs. Mistrust." Kevin Khatchadourian, the novel's central character, serves as a lens through which to explore the psychological dynamics of trust and mistrust in infancy and early childhood. The narrative provides a compelling portrayal of maternal ambivalence, strained parent-child relationships, and the consequences of mistrust within the family unit. Through a thorough analysis of the novel's characters and their interactions, this paper delves into how trust vs. mistrust unfolds, highlighting the lasting impact of early experiences on an individual's psychosocial development. By exploring the interplay between Kevin's character and Erikson's developmental theory, this paper offers valuable insights into the complex nature of human relationships and their role in shaping individual identity and behaviour.